Three-dimensional neuroblastoma cell culture: proteomic analysis between monolayer and multicellular tumor spheroids - Kumar, Hari R. (2008)
INTRODUCTION: Solid tumors, such as neuroblastoma (NB), are associated with a heterogeneous cell environment. Multicellular tumor spheroid (MCTS) cultures have been shown to better mimic growth characteristics of in vivo solid tumors. Because tumor spheroid growth patterns may be quite different from standard two-dimensional culture systems, we sought to compare the protein expression profiles of two- and three-dimensional in vitro NB cultures, i.e., monolayers and MCTS. MATERIALS AND METHODS: Human NB cells were grown as both monolayers and spheres. Nuclear and cytosolic proteins were analyzed for differentially secreted proteins by two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) and selected polypeptides were identified by mass spectrometry (LC-MS/MS). RESULTS: Several metabolic (transketolase, triosephosphate isomerase, pyruvate kinase M1/M2, alpha enolase, and phosphoglycerate mutase-1), cell stress response (heat shock proteins (HSP) 90, 70, and 60; antioxidant, thioredoxin), cell structure (septin 2, adenyl cyclase-associated protein-1), tubulin β-2 chain, actin, translationally controlled tumor protein and cofilin), signal transduction (peptidyl prolyl cis/trans isomerase A), biosynthetic (phosphoserine aminotransferase) and transport (cellular retinoic acid binding protein 1) polypeptides were over-expressed in spheroids. Several protein groups were differentially expressed between NB monolayers and spheroids. CONCLUSION: The altered proteins among NB spheroids may represent an important link between monolayer cell cultures and in vivo experiments and thus a more ideal in vitro culture system for determining the precise three-dimensional microenvironment of NB.